2018
DOI: 10.1088/1361-6528/aad881
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen out-diffusion and compositional changes in zinc oxide during ytterbium ions bombardment

Abstract: Oxygen release and out-diffusion in zinc oxide crystals during heavy ions bombardment has been suggested by many experimental techniques. In this work we have employed secondary ion mass spectrometry to study ZnO implanted with ytterbium ions. Our measurements confirm formation of an oxygen-depleted layer and oxygen out-diffusion and agglomeration at the surface. Moreover, an average compositional change in a heavily damaged near-surface region can also be monitored. This reproducible measurement procedure wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…4(b). Notably, compressive strain buildup was previously observed in ZnO implanted with Yb + ions and authors suggested that this effect is attributed to the lattice parameter decrease due to ion-induced oxygen loss from the implanted layer [33]. This mechanism cannot be excluded despite that the oxygen loss should be more pronounced for higher irradiation temperature potentially leading to the higher strain, which is not the case in Fig.…”
Section: Please Cite This Article As Doi: 101063/50051047mentioning
confidence: 80%
“…4(b). Notably, compressive strain buildup was previously observed in ZnO implanted with Yb + ions and authors suggested that this effect is attributed to the lattice parameter decrease due to ion-induced oxygen loss from the implanted layer [33]. This mechanism cannot be excluded despite that the oxygen loss should be more pronounced for higher irradiation temperature potentially leading to the higher strain, which is not the case in Fig.…”
Section: Please Cite This Article As Doi: 101063/50051047mentioning
confidence: 80%
“…The formation of an O deficient region between the sample surface and R p implanted ions was also recently reported for Yb implanted ZnO single crystals by high resolution SIMS measurements. 42 One of the possible reasons for the formation of open volume defects can be related to local stoichiometric disturbances in the collision cascades. 43 Therefore, an enhanced concentration of O vacancies is expected in the near surface region and this process can affect both Li and dopant redistribution after annealing, as demonstrated recently in Ref.…”
Section: Journal Of Applied Physicsmentioning
confidence: 99%